Managing Injuries of the Neck Trial (MINT): a randomised controlled trial of treatments for whiplash injuries. - Lamb, S; Williams, M; Williamson, E; Gates, S; Withers, E; Mt-Isa, S; Ashby, D; Castelnuovo, E; Underwood, M; Cooke, M (2012)
OBJECTIVES: To examine the clinical effectiveness of a stepped care approach over a 12-month period after an acute whiplash injury; to estimate the costs and cost-effectiveness of each strategy including treatments and subsequent health-care costs; and to gain participants' perspective on experiencing whiplash injury, NHS treatment, and recovery within the context of the Managing Injuries of the Neck Trial (MINT). DESIGN: Two linked, pragmatic, randomised controlled trials. In Step 1, emergency departments (EDs) were cluster randomised to usual care advice (UCA) or The Whiplash Book advice (WBA)/active management advice. In Step 2, participants were individually randomised to either a single session of advice from a physiotherapist or a physiotherapy package of up to six sessions. An economic evaluation and qualitative study were run in parallel with the trial. SETTING: Twelve NHS trusts in England comprising 15 EDs. PARTICIPANTS: People who attended EDs with an acute whiplash injury of whiplash-associated disorder grades I-III were eligible for Step 1. People who had attended EDs with whiplash injuries and had persistent symptoms 3 weeks after ED attendance were eligible for Step 2. INTERVENTIONS: In Step 1, the control intervention was UCA and the experimental intervention was a psycho-educational intervention (WBA/active management advice). In Step 2 the control treatment was reinforcement of the advice provided in Step 1 and the experimental intervention was a package of up to six physiotherapy treatments. MAIN OUTCOME: The primary outcome was the Neck Disability Index (NDI), which measures severity and frequency of pain and symptoms, and a range of activities including self-care, driving, reading, sleeping and recreation. Secondary outcomes included the mental and physical health-related quality-of-life (HRQoL) subscales of the Short Form questionnaire-12 items (SF-12) and the number of work days lost. RESULTS: A total of 3851 patients were recruited to Step 1 of the trial. 1598 patients attending EDs were randomised to UCA, and 2253 were randomised to WBA/active management. Outcome data were obtained at 12 months for 70% and 80% of participants at Step 1 and Step 2, respectively. The majority of people recovered from the injury. Eighteen per cent of the Step 1 cohort had late whiplash syndrome. There was no statistically or clinically significant difference observed in any of the outcomes for participants attending EDs randomised to UCA or active management advice [difference in NDI 0.5, 95% confidence interval (CI) -1.8 to 2.8]. In Step 2 the physiotherapy package resulted in improvements in neck disability at 4 months compared with a single advice session, but these effects were small at the population level (difference in NDI -3.2, 95% CI -5.8 to -0.7). The physiotherapy package was accompanied by a significant reduction in the number of work days lost at 4-month follow-up (difference -40.2, 95% CI -44.3 to -35.8). CONCLUSIONS: MINT suggests that enhanced psycho-educational interventions in EDs are no more effective than UCA in reducing the burden of acute whiplash injuries. A physiotherapy package provided to people who have persisting symptoms within the first 6 weeks of injury produced additional short-term benefits in neck disability compared with a single physiotherapy advice session. However, from a health-care perspective, the physiotherapy package was not cost-effective at current levels of willingness to pay. Both experimental treatments were associated with increased cost with no discernible gain in health-related quality of life. However, an important benefit of the physiotherapy package was a reduction in work days lost; consequently, the intervention may prove cost-effective at the societal level. TRIAL REGISTRATION: Current Controlled Trials ISRCTN33302125. FUNDING: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 16, No. 49. See the HTA programme website for further project information.